Reflections on Indigenous sovereignty - Kukutai, Tahu (Journal of Indigenous Wellbeing, 2019)
Keywords: data; data sovereignty; indigenous data sovereignty

Tracing Opuatia: Repatriating and repurposing colonial land data - Kukutai, Tahu; Whitehead, Jesse; Kani, Heeni (New Zealand Geographer, 2022)
Māori land data produced through colonial systems of dispossession lack interoperability, preventing kin-based communities from tracking their land. Our novel approach to repatriate and harmonise historic land data traces the history of the 45,500 acre Opuatia Block allocated to hapū Ngāti Tiipa in 1866, following the confiscation of 1.2 million acres of Waikato land. Ngāti Tiipa resisted Crown and settler pressures for 30 years, but 80% of Opuatia was alienated within a decade. We discuss the devastation of ‘judicial raupatu’ and the implications of this work for hapū data sovereignty and wider international efforts to achieve Indigenous data sovereignty.
Keywords: colonisation; data sovereignty; hapū; indigenous data sovereignty; iwi; māori land data; repatriation

Indigenous Peoples' Data During COVID-19: From External to Internal - Carroll, Stephanie Russo; Akee, Randall; Chung, Pyrou; Cormack, Donna; Kukutai, Tahu; Lovett, Raymond; Suina, Michele; Rowe, Robyn K. (Frontiers in Sociology, 2021)
Global disease trackers quantifying the size, spread, and distribution of COVID-19 illustrate the power of data during the pandemic. Data are required for decision-making, planning, mitigation, surveillance, and monitoring the equity of responses. There are dual concerns about the availability and suppression of COVID-19 data; due to historic and ongoing racism and exclusion, publicly available data can be both beneficial and harmful. Systemic policies related to genocide and racism, and historic and ongoing marginalization, have led to limitations in quality, quantity, access, and use of Indigenous Peoples' COVID-19 data. Governments, non-profits, researchers, and other institutions must collaborate with Indigenous Peoples on their own terms to improve access to and use of data for effective public health responses to COVID-19.
Keywords: colonisation; covid-19; data; data sovereignty; inequity; racism; self-determination

Recognition and indigenizing official statistics: Reflections from Aotearoa New Zealand and Australia - Kukutai, Tahu; Walter, Maggie (Statistical Journal of the IAOS, 2015)
In First World colonised nations such as Aotearoa New Zealand and Australia, population statistics form the evidentiary base for how Indigenous peoples are known and `managed' through state policy approaches. Yet, population statistics are not a neut
Keywords: colonisation; crown policy; data sovereignty; identity; policy; self-determination; statistics

Rights, interests and expectations: Indigenous perspectives on unrestricted access to genomic data - Hudson, Maui; Garrison, Nanibaa’ A.; Sterling, Rogena; Caron, Nadine R.; Fox, Keolu; Yracheta, Joseph; Anderson, Jane; Wilcox, Phil; Arbour, Laura; Brown, Alex; Taualii, Maile; Kukutai, Tahu; et al. (Nature Reviews Genetics, 2020)
Addressing Indigenous rights and interests in genetic resources has become increasingly challenging in an open science environment that promotes unrestricted access to genomic data. Although Indigenous experiences with genetic research have been shaped by a series of negative interactions, there is increasing recognition that equitable benefits can only be realized through greater participation of Indigenous communities. Issues of trust, accountability and equity underpin Indigenous critiques of genetic research and the sharing of genomic data. This Perspectives article highlights identified issues for Indigenous communities around the sharing of genomic data and suggests principles and actions that genomic researchers can adopt to recognize community rights and interests in data.
Keywords: crown law; data sovereignty; ethics; genes; genetic databases; genomic sequencing; population genetics

The Problem of Defining an Ethnic Group for Public Policy: Who is Māori and Why Does it Matter? - Kukutai, Tahu (Social Policy Journal of New Zealand, 2004)
Governments in multicultural democracies are increasingly being challenged to justify the collection of ethnic and racial data, and the targeted policies they support. Given mounting opposition to ethnicbased policies in New Zealand, it is timely to consider two questions that have arisen from ongoing debate. The first is what criteria ought to apply to determine who is Mäori for policy purposes. The second is which Mäori ought to benefit from targeted policies and programmes. This paper addresses both questions empirically and makes two suggestions: (1) that statistical and legal definitions of Mäori be amended to take account of both self-identified ethnicity and descent; (2) that programmes which seek to militate Mäori disadvantage be oriented towards those who strongly identify as Mäori, since they are the most likely to be in need.
Keywords: Inequity; data sovereignty; identity; policy; self-identification